USING THE “BRIEF” METHOD IN PREPARING FUTURE DESIGNERS FOR PROFESSIONAL ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS - Omonova Sarvinoz Halim qizi (Journal Park Publishing, 2025)
This article highlights the use of innovative educational technologies in teaching design project disciplines to students in higher education institutions. It focuses on preparing students for professional situations based on quasi-professional tasks. The effectiveness of developing future designers’ marketing and communication competencies through the “Brief” method is substantiated by the results of practical experimental work.